High peatland methane emissions following permafrost thaw: enhanced acetoclastic methanogenesis during early successional stages ... - Heffernan, Liam (Borealis, 2021)
The data provided in one xlsx file has six tabs: read me, porewater chemistry, enzymes, GHG fluxes, flux isotopes, dissolved gas concentrations and isotopes. "Read me" contains descriptions of all column headers and data. It provides units of measurement for each. ...